Effective separation and recovery of valuable metals from high value-added lead anode slime by sustainable vacuum distillation. (15th October 2021) - Yi, Jiafei; Zha, Guozheng; Huang, Daxin; Kong, Xiangfeng; Yang, Bin; Liu, Dachun; Xu, Baoqiang
Abstract: High value-added lead anode slime (LAS) contains valuable Ag and Au, as well as high levels of harmful elements, mainly As, Sb and Te. Traditional LAS pyrometallurgical treatment, which is a complex Pb and Sb extraction flow used for precious metal recovery, has exhausted energy sources and discharged hazardous wastes that have an increasingly harmful impact on the environment. Therefore, vacuum distillation for recovering Ag and Au from LAS has been investigated. Theoretical analysis shows that the rapid and effective recovery of valuable metals from LAS can be realized. At a temperature of 1173 K and a holding time of 2.5 h in a kilogram-scale experiment, Ag and Au were effectively enriched, and the recovery efficiencies were 92.10% and 96.85%, respectively; moreover, removal rates of 90.22% for As, 65.83% for Sb, and 98.48% for Te were achieved. The phase transformation of LAS before and after the vacuum distillation process was analyzed. The volatiles can serve as a raw material to produce Sb white, while the residue can be returned to the smelting-vacuum process for Au and Ag purification. In this vacuum distillation process, no gas or wastewater is discharged, thereby recycling valuable metals in a sustainable and clean manner. Graphical abstract: Image 1 Highlights: Clean separation of valuable metals from hazardous lead anode slime was investigated. Vacuum separation effect of alloy and oxide mixed components was firstly predicted. One-step distillation successfully enriched Ag and Au whilst obtaining Sb2 O3 and As2 O3 . Traditional complex process was simplified to one-step distillation and subsequent refining.